1980
DOI: 10.1002/j.1552-4604.1980.tb01670.x
|View full text |Cite
|
Sign up to set email alerts
|

Uricosuric Effect of Fenofibrate in Healthy Volunteers

Abstract: The uricosuric properties of a single oral dose (300 mg) of fenofibrate, or isopropyl-[4'-(p-chlorobenzoyl)-2-phenoxy-2-methyl] propionate (LF 178), a new hypolipidemic drug, have been investigated versus placebo, benzbromarone, with and without urine alkalinization, in ten normouricemic male volunteers, following a crossover design. Twofold increased uric acid clearance values were obtained after fenofibrate and fourfold increased values after benzbromarone. The ratio urinary uric acid/urinary creatinine (UUA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 6 publications
2
23
0
1
Order By: Relevance
“…The decrease of serum uric acid levels concomitant with the increase of uric acid clearance indicates that fenofibrate reduces serum uric acid levels by enhancing the urinary excretion of uric acid, as previously reported (7,8).…”
Section: Gout and Hyperuricemia Were Associated With Hyperlipidemia Isupporting
confidence: 84%
See 1 more Smart Citation
“…The decrease of serum uric acid levels concomitant with the increase of uric acid clearance indicates that fenofibrate reduces serum uric acid levels by enhancing the urinary excretion of uric acid, as previously reported (7,8).…”
Section: Gout and Hyperuricemia Were Associated With Hyperlipidemia Isupporting
confidence: 84%
“…Since approximately 1980, fenofibrate, a fibrate-type antihyperlipidemia drug, has been reported to decrease the serum concentration of uric acid via an enhanced urinary excretion of uric acid (7,8), but the detailed mechanism has remained unclear. Recently, Enomoto et (9).…”
Section: Hyperuricemia Frequently Is Associated With Hypertension Andmentioning
confidence: 99%
“…Calcium channel blockers and losartan are mildly uricosuric, unlike β blockers and other angiotensin II receptor antagonists, and both have been associated with a significant ly reduced risk of incident gout in a community based case control study. 88 The lipid lowering agent fenofibrate 89 and statins 90 are also mod estly uricosuric and should be considered when prescribing treatment for hyperlipidemia in pa tients with gout. Losartan (50 mg/d) and feno fibrate (300 mg/d) both had some additional Conclusions Surprisingly, the recommendation to eliminate urate crystals through lifelong low ering of SU below a target level, which is one of the overarching EULAR principles, and a key rec ommendation in all guidelines for the manage ment of gout from international rheumatology societies, 6,65,92,93 has recently been challenged in a clinical practice guideline from the American College of Physicians (ACP).…”
mentioning
confidence: 99%
“…To analyze CA, FA and Beza by chromatography, CH 3 Validation confirmed that this LC-MS/MS assay method met our needs for metabolite quantification. The analytes and the ISs were fully separated, as shown in Figure 2.…”
Section: Lc-ms/ms Assaymentioning
confidence: 64%
“…Fibrates have been used for decades to treat dyslipidemia. Clofibrate and fenofibrate are prodrugs that are hydrolyzed to clofibric acid (CA) and fenofibric acid (FA) in vivo [1][2][3]. In contrast, gemfibrozil (Gem) and bezafibrate (Beza) are active compounds.…”
mentioning
confidence: 99%